IMPLEMENTATION OF K13 LEARNING EVALUATION GRADE IV IN PRIMARY SCHOOL AND MADRASAH IBTIDAIYAH - Astuti, Mardiah; Anjani, Adelia Putri; Abdillah, Althaafi; Amalia, Riska; Pratiwi, Siska (LP2M IAI Al-Khairat Pamekasan, 2023)
This study aims to analyze the implementation of K-13 learning evaluation for grade 4 SD/MI. The method used in this study is qualitative with descriptive methods and case study approaches. The implementation of this research consisted of conducting interviews involving classroom teachers as resource persons with 5 question points. The curriculum is a reference for all learning activities to achieve educational goals. In its implementation, student learning outcomes are obtained during the learning process and learning outcomes, namely at the time of learning evaluation. The results of the study show that the implementation of the K-13 grade IV curriculum learning evaluation in SD/MI runs as it should, the evaluation has its forms of assessment, at the time of the application the teacher finds obstacles that are obstacles for the student in understanding the material being taught, with these obstacles the teacher tries to find a solution to the problem that exists so that the goal of the teaching can be achieved.